Chemical Investigation of Fatty Oil of Bursera penicillata Seed - , Theagarajan; Prabhu, V. V. (Indian Forester, 1983)
Bursera penicillata (sny. B. delpechiana) commonly known as Indian Linaloe or Indian lavender is an exotic, introduced into India, and is at present one of the most important essential oil yielding plants. The essential oil is obtained from the fruit husk and the seed as such has not been put to any use at present, although it is available to the extent of about 5 tonnes every year. An examination of the seed has shown that it contains a ratty oil (17-18% yield on the wt. of the Whole seed) whose compostion has indicated that it belongs to the normal type of fatty all. The oil is composed essentially of the glycerides of the following fatty acids: myristic, palmitic, stearic, oleic and linoleic. Its physico-chemical characteristics have also been determined. It can serve as a suitable raw material for the soap industry.